Malnutrition risk and oropharyngeal dysphagia in the chronic post-stroke phase - Huppertz, V. A. L.; Pilz, W.; Pilz Da Cunha, G.; de Groot, L. C. P. G. M.; van Helvoort, A.; Schols, J. M. G. A.; Baijens, L. W. J. (Frontiers in Neurology, 2022)
Background Oropharyngeal dysphagia (OD) and malnutrition are associated with poor clinical outcomes after stroke. The present study evaluated (1) malnutrition risk and OD-related characteristics in patients with chronic post-stroke OD, and (2) the relationship between on the one hand OD severity and on the other hand functional oral intake and dysphagia-specific quality of life. Methods A cross-sectional study was conducted in a Dutch interdisciplinary outpatient clinic for OD. The standardized examination protocol comprised: clinical ear, nose, and throat examination, body mass index, the short nutritional assessment questionnaire (SNAQ), a standardized fiberoptic endoscopic evaluation of swallowing (FEES), the functional oral intake scale (FOIS), and the MD Anderson dysphagia inventory (MDADI). Results Forty-two consecutive patients with chronic post-stroke OD were included. Mean (±SD) age and BMI of the population were 69.1 (±8.7) years and 26.8 (±4.1) kg/m2 respectively. Seventeen (40.4%) patients presented a moderate to high risk of malnutrition (SNAQ score≥2). The FEES examination showed moderate to severe OD in 28 (66.7%) patients. The severity of OD was significantly related to the FOIS score but not to the MDADI scores. Conclusion In this specific sample of referred stroke patients, moderate to severe OD and moderate to high risk of malnutrition were common. Despite the use of clinical practice guidelines on stroke and a normal nutritional status at first sight, repeated screening for malnutrition and monitoring the severity and management of OD remain important elements in the care of patients with chronic post-stroke OD.